2017
DOI: 10.1055/s-0043-103573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on the Androgenic Profile in Patients with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: It is suggested that vitamin D status is associated with androgenic profile in women with polycystic ovarian syndrome (PCOS). Although several clinical trials are known in this regard, the results were inconsistent. Therefore, this study was aimed to conduct a systematic review and meta-analysis of published clinical trials to elucidate the possible effect of vitamin D supplementation on the androgen levels in adult females with PCOS. PubMed, SCOPUS, and Google Scholar were searched to identify related article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 30 publications
2
47
2
1
Order By: Relevance
“…With regard to SHBG, the positive relationship with vitamin D concentration that we observed is consistent with results observed previously among both women with PCOS 22,23 and postmenopausal women. 14,24 However, our positive finding conflicts with results from the aforementioned meta-analysis; 21 our study’s larger cohort (and therefore greater power) may also explain why we found a relationship between vitamin D and SHBG while the meta-analysis did not.…”
Section: Commentcontrasting
confidence: 90%
See 1 more Smart Citation
“…With regard to SHBG, the positive relationship with vitamin D concentration that we observed is consistent with results observed previously among both women with PCOS 22,23 and postmenopausal women. 14,24 However, our positive finding conflicts with results from the aforementioned meta-analysis; 21 our study’s larger cohort (and therefore greater power) may also explain why we found a relationship between vitamin D and SHBG while the meta-analysis did not.…”
Section: Commentcontrasting
confidence: 90%
“…13 A systematic review and meta-analysis of vitamin D supplementation among a total of 183 women with PCOS found that supplementation with vitamin D significantly reduces TT. 21 Our null results may differ from these studies because our population was, respectively, eumenorrheic, premenopausal, and not being supplemented with vitamin D.…”
Section: Commentcontrasting
confidence: 67%
“…Seven reviews evaluated vitamin D (Appendix S3, found in the Supporting Information) either as monotherapy vs placebo or metformin, as combination therapy with metformin vs metformin or comparing the effects of before and after vitamin D. Only one review had a high rating while the majority of the reviews (n = 5) were of moderate quality, and one review was of low quality. A total of 75 trials and 5701 participants women with PCOS were involved.…”
Section: Resultsmentioning
confidence: 99%
“…137 Some studies have demonstrated lower serum vitamin D concentrations in women with PCOS compared to women without PCOS, whereas a case-control study, with 85 women with PCOS and 115 healthy controls, found higher serum vitamin D concentrations in women with PCOS compared to controls. [138][139][140] Low serum vitamin D levels or insufficiency has been positively associated with PCOS-related symptoms, such as central obesity, IR, infertility and hirsutism, whereas serum 25-hydroxy vitamin D (25OHD) seems to be an independent predictor of measures of reproductive success following ovulation induction.…”
Section: Vitamin D and Pcosmentioning
confidence: 99%
“…[141][142][143][144] A recent systematic review and meta-analysis showed that vitamin D supplementation significantly decreased total testosterone, without any effects on serum SHBG and free testosterone. 137 Another systematic review discussed the association between vitamin D status and metabolic disturbances and suggested an inverse association between vitamin D status and IR in women with PCOS. 145 One study showed that 1000 mg/day calcium plus 50,000 IU/week vitamin D supplementation for 8 weeks among vitamin D-deficient women with PCOS had beneficial effects on serum insulin levels, IR, TG and very-LDL (VLDL) levels, without affecting fasting glucose and other lipid profiles.…”
Section: Vitamin D and Pcosmentioning
confidence: 99%